2015
DOI: 10.3233/jrs-150676
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4 activity and haloperidol effects in alcohol addicts

Abstract: It should be noted that in this research the activity of CYP3A4 was determined using high performance liquid chromatography with mass spectrometry (HPLC/MS) by determination the ratio of cortisol/6-beta-hydroxycortisol for the fist time. To increase the level of our confidence in the results further studies with a larger number of people are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…In our previous works, we showed the effect of CYP2D6 polymorphism (and its activity)21 and the activity of CYP3A428 on haloperidol efficacy and safety.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous works, we showed the effect of CYP2D6 polymorphism (and its activity)21 and the activity of CYP3A428 on haloperidol efficacy and safety.…”
Section: Discussionmentioning
confidence: 98%
“…Other risk factors for dystonia are male gender, black race, hypocalcaemia, hypoparathyroidism and dehydration 1. There is also a higher risk of extrapyramidal symptoms (EPS) in alcohol addicts due to the same metabolism pathway via cytochrome P450 7. Nevertheless, there is no sufficient data for ‘binge drinking’ consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous research demonstrated that CYP3A4 and CYP3A5 have common substrates 21,22 and that endogenous cortisol transforms to 6-beta-hydroxicortisol (6-b-HC) selectively by CYP3A isoenzyme, the metabolic ratio of 6-b-HC/ cortisol in urine can be used to evaluate the activity of CYP3A. 23 In our study, to evaluate CYP3A enzymatic activity, we determined the urinary concentration of endogenous substrate of the enzyme and its metabolite, 6-b-HC to cortisol ratio, [24][25][26][27][28] using high-performance liquid chromatographymass spectrometry (HPLC-MS/MS). [29][30][31] The results of the isoenzymes evaluation are demonstrated in arbitrary units.…”
Section: Phenotypingmentioning
confidence: 99%